Redox robustness drives LPMO evolution - Iván Ayuso-Fernández; Tom Z. Emrich-Mills; Ole Golten; Zarah Forsberg; Kelsi R. Hall; László G. Nagy; Morten Sørlie; Åsmund Kjendseth Røhr; Vincent G. H. Eijsink (Proceedings of the National Academy of Sciences, 2026)
Enzymes known as lytic polysaccharide monooxygenases (LPMOs) are exceptionally powerful small redox enzymes that master the controlled generation and productive use of potentially damaging hydroxyl radicals in what is essentially a H 2 O 2 -driven peroxygenase reaction. We have used ancestral sequence reconstruction and enzyme resurrection to unravel evolutionary steps leading to this exceptional catalytic ability. Real-time monitoring of copper reoxidation and amino acid radical formation showed evolutionary improvement of both the capacity to avoid futile turnover of H 2 O 2 and the ability to scavenge damaging radicals resulting from such turnover through a hole hopping pathway. Through mutational studies of ancestral LPMOs, we show that adoption of an extant-like conformation of residues in the hole hopping pathway yields improvements in redox robustness to near-extant levels. These results show how selective pressure imposed by the need for generating a highly oxidizing intermediate is a key driver of metalloenzyme evolution, involving large parts of the enzyme, well beyond the catalytic center.